Notre-Dame du Raincy (Seine-Saint-Denis), chef-d’œuvre des chapelles de la banlieue ? - Antoine Le Bas (In Situ)
The Paris suburb of Le Raincy became an independent commune in 1869 and, in accordance with the Concordat of 1801, was expected to build a church to accommodate its growing numbers of parishioners. After the First World War, the parish priest, Victor Nègre, received a donation destined to honour the victims of the Battle of the Marne, and the church he had to conceive was consequently both a parish church and a war memorial. After various other projects, the architects Auguste and Gustave Perret put forward a design for a vast, airy building which could be erected at a relatively low cost. Their building was of basilical inspiration with a fairly traditional tower-porch. But the church was nonetheless a highly innovative building in terms of its construction techniques: the thin concrete walls for the nave and side aisles; the use of reinforced concrete, then almost unheard of in religious architecture; the building techniques used, based on considerable standardisation in the production and assembly of modular elements. The church took thirteen months to build and resulted in an edifice with all the facilities necessary for parish life, but which was also a sanctuary in harmony with the liturgical reforms undertaken at the beginning of the 20th century. The decoration of the church was particularly rich, resulting from the close collaboration between the priest, the architects and the painter Maurice Denis. The themes dealt with, turning around the figures of Christ and the Virgin Mary, and with patriotic overtones, announced in their synthesis the inter-war renewal of sacred art. Despite initial reticence in the face of the church’s modernity, it was soon recognised, first abroad and then in France, as a possible prototype for modern, economic religious buildings. The Perret brothers pursued this type of church building, with numerous examples, up to the end of their career. The recognition of the church’s heritage values - it was given statutory protection (classé) in 1966 - guaranteed the building’s survival: the original reinforced concrete and the stained-glass windows were in urgent need of restoration, but this restoration has been completed today.